DESKRIPSI KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA MATERI PECAHAN DITINJAU DARI GAYA BELAJAR PADA SISWA KELAS VII MTs PERGIS GANRA - Muhlisa, Nurul; Syamsuadi, Ahmad; Satriani, Sri (Almeera Education, 2023)
The purpose of this study was to determine and analyze the mathematical problem solving ability of fractions in terms of learning styles in the seventh grade students of MTs Peris Ganra. Indicators of problem solving ability used in this study are (1) understanding the problem; (2) make a settlement plan; (3 carry out the plan; and (4) re-examine. Meanwhile, the visual learning style, auditory learning style, and kinesthetic learning style.This type of research is a qualitative descriptive approach. The research was carried out at MTs Peris Ganra Jl. Ganra sub-district education, Soppeng Regency. The subjects in this study amounted to 3 students who represented each of each learning style. The instruments used in this research are learning style questionnaires, problem solving tests, and interview guidelines. The results of this study indicate that (1) visual subjects are able to understand the problem, are able to make plans, are able to carry out plans, and are able to make conclusions and re-evaluate the final results obtained. (2) Auditory subjects are able to understand problems, are able to make plans, are able to carry out plans, and are able to draw conclusions and re-evaluate the final results obtained. (3) Kinesthetic subjects are able to understand problems, are able to make plans, and are able to carry out plans but do not make conclusions and re-evaluating because in working on the questions students are not able to write plans before completing the completion steps on the questions and also do not re-examine the final results obtained.